A Study on Production Practices and Profitability of Leafy Vegetable Farming in Peri-Urban Colombo, Sri Lanka - Peiris, P.S.M.; Weligamage, Parakrama (Sri Lanka Association for the Advancement of Science, Colombo 07, 2015)
The demand for leafy vegetables has recently increased due to increasing consumer incomes and the widening of dietary diversity. The highly perishable nature of this vegetable group has led to the development of peri-urban areas as major production areas. This has implications on agricultural land use patterns and sources of income for farmers. Despite the abundance of research on production and marketing of other vegetables in Sri Lanka, there is a paucity of studies on the economics of leafy vegetable production and marketing. The objectives of this research were to a) document production practices, and b) to calculate farm profitability of leafy vegetable farming in a peri-urban production area of Sri Lanka. A farm level study was conducted in two villages selected from the Bolgoda Lake periphery in the Kalutara District. Located in the South of Colombo, the major urban market in the country, this area is a major supply area of leafy vegetables to the city. A sample of 32 farmers was selected randomly from the two villages for the study. Data on farming practices; quantities of inputs and outputs, and costs and revenues were collected using a structured survey schedule. Crop enterprise budgets were computed to compare profitability among different leafy vegetable crops. According to the results, about two thirds of farmers practice multiple cropping and concurrently grow two to six crops leading to ten crop combinations. Average farm size is 0.5 ha. Kan-kun (Ipomea aquatica); mukunuvenna (Alternanthera sessilis) and gotukola (Centella asiatica) account for 85% of the area under leafy vegetables. Kan-kun is the most popular mono-cropped leafy vegetable as it is grown by 22% of farmers. It is also the crop with the highest plot size with mean plot size of 0.14 ha. Results of crop enterprise budget analysis indicate that kan-kun is the crop with the highest unit profits around LKR 1.5 million/ha/cropping round. Unit profits for gotukola and mukunuwenna are LKR “000” 942 and 287 per ha per cropping round respectively. This analysis concludes that cultivation of leafy vegetables is profitable and generates substantial incomes to small famers in per-urban areas.
Keywords: Farm budgeting; multiple cropping; irrigated farming; ratoon crops; farm income; Kalutara District